(3cTa GdhGajI aj TQM GdcGajIs - (3GdMdHj, eMeO Hf YeQ SQGL GdOjf, J (B850(3g`s
(3ChdgG (B:s
(3CeG HYO agPg GdhcI (B((3cPG(B) (3eTJedI Ydi CLhHI GdCfXGQ GdJj ChQOgG UGMH GdhGajI aj TQM GdcGajI Ydi GdQSGdI GdefShHI Edi GHf GdMGLH HQO Gddg bHQg hLYdg eNdOG aj OGQ GdLfGfs
(3BNQgG (B:s
(3hEf cGf XGgQG ZjQ Mbjbj aeNHQ Ydi Cf GdSHH ddMhb JGA JCfjK GdaGYd adG JcQGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 315s
(3eYLe GdeDdajf(B: 3 / 560s
(3cTa GdXfhf(B: 2 / 1370s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs